Sleep Quality and Immune Mediators in Asthmatic Children - Ming-Fuu Wang (Elsevier, 2009)
Asthmatic children have been reported to complain about poor sleep quality. Recent research has demonstrated a relationship between sleep and circulating cytokines. This study aimed to assess the relationship between serum cytokine levels and sleep quality in asthmatic children. Methods: After an initial screening phase at allergy clinic visits, 90 asthmatic children aged 6-12 years were enrolled to complete the Chinese version of the (Childhood) Asthma Control Test (ACT). A questionnaire assessing sleep quality of asthmatic children was also administered to all subjects and parents. We determined the serum levels of interleukin (IL)-4, IL-6, IL-10, IL-12, total immunoglobulin (Ig) E, and prolactin at enrollment. Results: Subjects with an ACT score ≥ 20 were assigned to the well-controlled group and those with a score of ≤ 19 were assigned to the inadequately controlled group. In the well-controlled group, good sleepers had a significantly lower mean level of IL-10 and a higher mean ratio of IL-12/IL-10 compared with the poor sleepers. Furthermore, the serum prolactin level was significantly greater in the good sleeper subgroup. In both subgroups, the concentrations of IL-6, IL-12 and total IgE were not significant different. Conclusion: Good sleep is associated with a lower IL-10 level, a higher prolactin concentration, and a higher IL-12/IL-10 ratio. Prolactin may have a potential role in this immunity shift. Thus, further insight into the functional role of cytokines on the sleep quality of asthma sufferers will result in the identification of novel therapeutic perspectives.